2020
DOI: 10.21203/rs.3.rs-26577/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Potential Role of Local Pharmacies to Assess Asthma Control: an Italian Cross-sectional Study

Abstract: Background. Asthma control and monitoring still represents a challenge worldwide. Although the international guidelines suggest the interplay with primary care as an effective strategy to control the disease, community pharmacies’ are seldom involved in asthma control assessment. The present cross-sectional study aimed at providing a picture of the relationship between asthma severity and control in community pharmacies of the health district of the city of Verona (Veneto Region, North-Eastern Italy).Methods. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Together with ERs, community pharmacies also represent a first-line health care service, which seems to be more easily accessed by asthmatics when compared to respiratory medicine specialists or general practitioners. 1 , 35 , 36 Patients easily refer to the pharmacy to get reliever medications or inhaled drugs in general and bypass the medical follow-up visit. However, a recent large study including community pharmacies confirmed that non-optimal asthma control was more frequent among patients with mild-to-moderate asthma and that low treatment adherence was the only determinant of poorly controlled asthma.…”
Section: Mild-to-moderate Asthma – Unmet Needs and Potential Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with ERs, community pharmacies also represent a first-line health care service, which seems to be more easily accessed by asthmatics when compared to respiratory medicine specialists or general practitioners. 1 , 35 , 36 Patients easily refer to the pharmacy to get reliever medications or inhaled drugs in general and bypass the medical follow-up visit. However, a recent large study including community pharmacies confirmed that non-optimal asthma control was more frequent among patients with mild-to-moderate asthma and that low treatment adherence was the only determinant of poorly controlled asthma.…”
Section: Mild-to-moderate Asthma – Unmet Needs and Potential Strategiesmentioning
confidence: 99%
“…However, a recent large study including community pharmacies confirmed that non-optimal asthma control was more frequent among patients with mild-to-moderate asthma and that low treatment adherence was the only determinant of poorly controlled asthma. 36 …”
Section: Mild-to-moderate Asthma – Unmet Needs and Potential Strategiesmentioning
confidence: 99%
See 1 more Smart Citation